2022
DOI: 10.1039/d1cc05195d
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometallated complexes as catalysts for C–H activation and functionalization

Abstract: This highlight describes an emerging trend in the C–H activation field: the use of the cyclometallated catalysts for the challenging and unprecedented direct transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…These results are in good agreement with the experiments, where free p -cymene was detected during the reaction. With regards to potential bis-cyclometalated intermediate, 26 the ruthenium( ii / iv ) manifold pathway was shown to be energetically preferred over the ruthenium( i / iii ) manifold pathway by 22.2 kcal mol −1 . Thus, our computational findings provide strong support for a preferential oxidatively induced reductive elimination through bis-cyclometalated ruthenium( iv ) species.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in good agreement with the experiments, where free p -cymene was detected during the reaction. With regards to potential bis-cyclometalated intermediate, 26 the ruthenium( ii / iv ) manifold pathway was shown to be energetically preferred over the ruthenium( i / iii ) manifold pathway by 22.2 kcal mol −1 . Thus, our computational findings provide strong support for a preferential oxidatively induced reductive elimination through bis-cyclometalated ruthenium( iv ) species.…”
Section: Resultsmentioning
confidence: 99%
“…For a complementary perspective on the involvement of metallacycles in C–H activation, readers are directed to a recent review by Wencel-Delord and coworkers. 38 …”
Section: C–h Functionalisationmentioning
confidence: 99%
“…In 2018, our group reported a direct C–H arylation procedure that was able to proceed at ambient temperature. 35–37 These studies revealed that the p -cymene ligand commonly found on ruthenium prevents formation of the necessary bis-cyclometallated Ru( ii ) species. As such, the use of arene-ligated-free mono-cyclometallated catalyst, RuBnN, led to a significant improvement in catalytic activity, allowing the use of mild reaction conditions, and compatibility with a wide range of coupling partners.…”
Section: Introductionmentioning
confidence: 99%